Mast Cell Activation Syndrome in COVID-19 and Female Reproductive Function: Theoretical Background vs. Accumulating Clinical Evidence. (22nd June 2022) - Szukiewicz, Dariusz; Wojdasiewicz, Piotr; Watroba, Mateusz; Szewczyk, Grzegorz
Abstract : Coronavirus disease 2019 (COVID-19), a pandemic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, can affect almost all systems and organs of the human body, including those responsible for reproductive function in women. The multisystem inflammatory response in COVID-19 shows many analogies with mast cell activation syndrome (MCAS), and MCAS may be an important component in the course of COVID-19. Of note, the female sex hormones estradiol (E2 ) and progesterone (P4) significantly influence mast cell (MC) behavior. This review presents the importance of MCs and the mediators from their granules in the female reproductive system, including pregnancy, and discusses the mechanism of potential disorders related to MCAS. Then, the available data on COVID-19 in the context of hormonal disorders, the course of endometriosis, female fertility, and the course of pregnancy were compiled to verify intuitively predicted threats. Surprisingly, although COVID-19 hyperinflammation and post-COVID-19 illness may be rooted in MCAS, the available clinical data do not provide grounds for treating this mechanism as significantly increasing the risk of abnormal female reproductive function, including pregnancy. Further studies in the context of post COVID-19 condition (long COVID), where inflammation and a procoagulative state resemble many aspects of MCAS, are needed.